Analysis of the Implementation of the Teaching Campus to Increase Student Learning Motivation at SDN Janji Pusuk in the Digital Era - Christyani Siregar; Bena br Ginting; Hermelina Ekasari Br Tarigan; Herlina Simangunsong; Dinaria br Sembiring (Outline Journal of Education, 2026)
This study aims to analyze the implementation of the Kampus Mengajar Program in enhancing students' learning motivation at SDN 175788 Janji Pusuk and SDN 177669 Onan Ganjang in the digital era. The Kampus Mengajar Program is an initiative by the Ministry of Education, Culture, Research, and Technology, involving university students as teachers to assist elementary school students. In the context of the digital era, this program is expected to utilize technology to improve the quality of learning and student motivation. The research employs a quantitative approach with data collection techniques through questionnaire, observation, interviews, and documentation. The subjects of the study include students, mentor teachers, and school principals. The data obtained are analyzed descriptively to illustrate the implementation of the program and its impact on students' learning motivation. In conclusion, the Kampus Mengajar Program is effective in improving students' learning motivation at SDN 175788 Janji Pusuk and SDN 177669 Onan Ganjang, particularly through the utilization of digital technology in the learning process. Recommendations from this study include the need for further support from schools and the government to expand access to technology and training for teachers and students, in order to maximize the potential of this program in enhancing the quality of education in the digital era.